2018
DOI: 10.3390/ijms19092626
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal Chaperones and miRNAs in Gliomagenesis: State-of-Art and Theranostics Perspectives

Abstract: Gliomas have poor prognosis no matter the treatment applied, remaining an unmet clinical need. As background for a substantial change in this situation, this review will focus on the following points: (i) the steady progress in establishing the role of molecular chaperones in carcinogenesis; (ii) the recent advances in the knowledge of miRNAs in regulating gene expression, including genes involved in carcinogenesis and genes encoding chaperones; and (iii) the findings about exosomes and their cargo released by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 143 publications
(194 reference statements)
0
31
0
Order By: Relevance
“…Many investigations have been done in the attempt to use chaperones for the corrections of protein misfolding and treatment of human diseases [41]. Among HSPs, HSP60 has been shown to be involved in brain tumors [1,[42][43][44], and preclinical in vitro and in vivo data have shown that curcumin may be an effective treatment for brain tumors [17]. Nevertheless, it remains to be explored what the effect of curcumin on HSP60 s expression and/or function is.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigations have been done in the attempt to use chaperones for the corrections of protein misfolding and treatment of human diseases [41]. Among HSPs, HSP60 has been shown to be involved in brain tumors [1,[42][43][44], and preclinical in vitro and in vivo data have shown that curcumin may be an effective treatment for brain tumors [17]. Nevertheless, it remains to be explored what the effect of curcumin on HSP60 s expression and/or function is.…”
Section: Discussionmentioning
confidence: 99%
“…The HSP60 secretion is linked to widespread intercellular communication events with various biologic effects. In brain tumors, HSP60 is overexpressed [68,69], and its secretion may be a mechanism involved in cell transformation and in tumor progression, suggesting that HSP60 is a potential therapeutic target for brain tumors treatment [42].…”
Section: Discussionmentioning
confidence: 99%
“…The intravesicular cargo may variate depending on the cell type that secretes them and according to their specific function on the recipient cell, such as cytokines [95], hormones [96], transcription factors, growth factors [97] and heat shock proteins [98][99][100][101][102][103][104][105][106][107]. Moreover, there is a large number of proteins that compose the structure of exosomes, which are directly involved in cell trafficking and their specificity: exosomes are enriched in proteins involved in the vesicles' trafficking, cell surface receptors such as tumor susceptibility gene 101 (TSG101); integrin and a number of tetraspanins such as CD9, CD53, CD63, CD81 and CD82 [108,109].…”
Section: Evsmentioning
confidence: 99%
“…HSPs have been reported to be a constant cargo feature of exosomes and other EVs. Hence, glioma cell‐derived EVs (especially exosomes) harboring an abundance of HSPs have a high potential for use in diagnostic purposes …”
Section: New Hope For Glioma Diagnosticsmentioning
confidence: 99%